Marco Aguilar, Through the Eyes of the Critic Alberto Cañas - Cañas, Alberto (2024)
This article corresponds to a judgment of major relevance, as it was written by the prominent literary critic Alberto Cañas in Chisporroteos, his weekly column in La República Newspaper. It was published in August 1996, to celebrate the launching of the book of sonnets El tránsito del sol (The Sun’s Transition), and in which the poetic quality of Marco Aguilar stands out, particularly as a writer of extraordinary sonnets, a modality that he revitalized with grace.